2019
DOI: 10.1177/1082013219825892
|View full text |Cite
|
Sign up to set email alerts
|

El Gueddid, a traditional Algerian dried salted meat: Physicochemical, microbiological characteristics and proteolysis intensity during its manufacturing process and ripening

Abstract: El Gueddid is a traditional salted and dried meat with high popularity in Algeria. It is used as an ingredient in various dishes. In this study, different samples of El Gueddid were analyzed at different processing times to follow up their microbiological and physico-chemical properties. Changes in the protein profile were also demonstrated by electrophoretic study of myofibrillar proteins. Microbiological determinations included the Total Viable Count, Coliforms, Staphylococci, Lactic Acid Bacteria, Yeasts an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…In our study the initial contamination (total aerobic counts) of the sliced fresh meat from different animal species was about 5 log CFU/g. This level agreed with the one already found for fresh sheep meat (Benlacheheb et al, 2019) and from fresh beef (Pinto et al, 2002) but was one log lower to the one found in raw pork meat (Lorenzo et al, 2015) and goat meat (Rahman et al, 2005). The total counts remained stable up to 90 days and then decreased along the process in the four El-Guedid studied.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study the initial contamination (total aerobic counts) of the sliced fresh meat from different animal species was about 5 log CFU/g. This level agreed with the one already found for fresh sheep meat (Benlacheheb et al, 2019) and from fresh beef (Pinto et al, 2002) but was one log lower to the one found in raw pork meat (Lorenzo et al, 2015) and goat meat (Rahman et al, 2005). The total counts remained stable up to 90 days and then decreased along the process in the four El-Guedid studied.…”
Section: Discussionsupporting
confidence: 91%
“…Finally, a third category of intermediate moisture products can be defined for charqui, jerky and dry cured ham (a w ranging from 0.70 to 0.83) (Marušić, Vidaček, Janči, Tomislav Petrak, & Medić, 2014;Pinto et al, 2002;Yang, Hwang, Joo, & Park, 2009). The initial pH values (pH 6.3-6.4) of the fresh meats from different animal origins in this study were close to those found by Benlacheheb et al (2019) in fresh lamb meat. These values decreased during the ripening reaching final values of 5.2 to 5.5, regardless the meat used.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The Kaddid or Gueddid is a traditional salty and dry meat product typically prepared from mutton meat salted and dried outdoors in Maghreb countries (Tunisia, Algeria and Morocco) [5]. The Gueddid can be stored at room temperature for more than a year, and, before consumption, it is desalted after immersion in water, being used in various dishes, such as Aiche, Couscous, Elhessa and Marloga in Algeria [26]. In addition to Gueddid, there are other dry and fermented or not fermented products of North Africa and the Mediterranean of sheep and goat meats, such as Kourdass (a sausage prepared from offal lamb stomach, intestines, liver, lung, spleen and fat), Tidkit (a sun-dried product), Boubnita (a dry lamb fermented sausage), Soudjouk or sucuk (a dry fermented and uncooked sausage of Turkish origin) or Maynama and Merdouma (smoked products) [5] In Southern Africa, a goat meat drying technique using salting and smoking processes and known as chinkui in Mozambique's Northern Tete Province is also commonly used [27] as a complementary source of protein in local rural areas of developing countries with large undernourished populations.…”
Section: Dried and Semi-dried Productsmentioning
confidence: 99%